2015
DOI: 10.3390/catal5020815
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of the Carbon Support to Synthesize Pt(Cu) and Pt-Ru(Cu) Core-Shell Electrocatalysts for Low-Temperature Fuel Cells

Abstract: Abstract:The synthesis of core-shell Pt(Cu) and Pt-Ru(Cu) electrocatalysts allows for a reduction in the amount of precious metal and, as was previously shown, a better CO oxidation performance can be achieved when compared to the nanoparticulated Pt and Pt-Ru ones. In this paper, the carbon black used as the support was previously submitted to electrochemical oxidation and characterized by XPS. The new catalysts thus prepared were characterized by HRTEM, FFT, EDX, and electrochemical techniques. Cu nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Inoue et al developed a new method without using any surfactant to synthesize clean Pd nanoparticles as the core for Pt monolayer deposition [20]. On the other hand, Caballero-Manrique et al used Cu nanoparticles as the sacrificing template to prepare core-shell catalysts consisting of Pt and PtRu shells [21]. Amra et al tried to explain the strain and ligand effects from the Pd1−xCux alloy core on the Pt monolayer based on the first principles density functional theory (DFT) calculations [22].…”
Section: This Special Issuementioning
confidence: 99%
“…Inoue et al developed a new method without using any surfactant to synthesize clean Pd nanoparticles as the core for Pt monolayer deposition [20]. On the other hand, Caballero-Manrique et al used Cu nanoparticles as the sacrificing template to prepare core-shell catalysts consisting of Pt and PtRu shells [21]. Amra et al tried to explain the strain and ligand effects from the Pd1−xCux alloy core on the Pt monolayer based on the first principles density functional theory (DFT) calculations [22].…”
Section: This Special Issuementioning
confidence: 99%
“…It is well known that platinum alloying with the base metals such as Ni, Co, Cu, etc. contributes to an increase in the functional characteristics of catalysts in methanol electrooxidation (MOR) and oxygen electroreduction ORR [6,[10][11][12][13][14]. The increase in the activity of bimetallic catalysts compared to Pt/C in the methanol electrooxidation reaction is usually explained by the bifunctional catalysis mechanism, in which OH groups adsorbed on the atoms of the doping component facilitate electrochemical desorption of the intermediate products of methanol oxidation from the Pt surface [6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the content of the precious metal in the bimetallic catalyst, while increasing its activity in current-forming reactions, attempts have been made to optimize the composition and structure of platinum-containing nanoparticles [10,13,[18][19][20][21][22][23][24]. Note that the features of the hierarchical structural organization of PtCu/C catalysts are determined not only by the shape and size of the metal nanoparticles, but also by their spatial distribution on the surface of the support, and have a crucial effect on the activity of catalysts in ORR and MOR [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…S8A †). [15][16][17] The N 1s peaks at 398.5, 399.7 and 401.5 eV showed that nitrogen existed mostly in the form of N-B, N-C and N-H, respectively (Fig. S8B †).…”
mentioning
confidence: 99%